Volume and comparative advantage in East-West trade - Parvati Trübswetter; Dieter Schumacher (Deutsches Institut für Wirtschaftsforschung (DIW), 2000)
The volume and commodity structure of EU trade with the transition countries in central and eastern Europe (CEECs) is estimated on the assumption that it will follow the pattern of trade among market economies. A gravity-type approach at the level of product groups is used, combining geography and factor-proportions theory of international trade. It is shown that there is still considerable potential for a further rise in East-West trade if the CEECs? national product is valued at purchasing power parities, instead of market exchange rates. Considering divergent income levels and distance between East and West, the EU?s comparative advantages are in specialised-supplier, scale-intensive and science-based goods, whereas the CEECs? comparative advantages are in labour-intensive and resource-intensive goods. The intersectoral specialisation pattern will become "flatter" and the share of intra-industry trade will grow when the income differentials decrease.
Keywords: F10; F17; 330; East-West trade; gravity model; comparative advantages; Ost-West-Beziehungen; Internationale Wirtschaftsbeziehungen; Außenhandelsstruktur; Komparativer Kostenvorteil; Gravitationsmodell; Schätzung; Ostmitteleuropa; EU-Staaten